ILRI's capacity strengthening strategy - International Livestock Research Institute (International Livestock Research Institute, 2008)
The spirit of this revised strategy is to continue to carry out training and capacity strengthening and promote learning compatible with ILRI’s research priorities and outputs and develop implementation of programs to do so in ways that strengthen, mobilize and sustain its partners capacities. The important strength of this strategy is that the preparation process was participatory, all inclusive, demand driven and is based on fi ve sub-regional training needs assessment studies of the livestock sector completed in 2007. The proposed strategy provides the fl exibility to develop targeted programs based on the priorities and it explicitly recognizes the inherent diversity in the capacity development needs. Systematic efforts are also made to identify gaps in both technical as well as soft skills needed to implement an effective, effi cient and impact oriented capacity strengthening program. The important departure is the explicit recognition of the need for ILRI to reorient its capacity strengthening activities to ‘changing institutes’ by ‘changing individuals’ rather than the latter alone as has been in the past. In addition to supporting the current research portfolio of ILRI, every effort will be made to address the emerging issues and contemporary challenges facing the livestock innovation systems in the developing countries and the associated capacity needs. To keep the strategy relevant and dynamic it will be updated periodically to refl ect the changing circumstances and needs of our partners.